Sistem Penentuan Jenis Kayu Untuk Furniture Menggunakan Metode TOPSIS Berbasis Web Pada Edogawa Furniture Depok - YOGA ALDIAN PUTRA YOGA ALDIAN PUTRA; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Wood is the main raw material or element, each of which has different qualities in the manufacture of furniture products. Edogawa Furniture Depok is the maker craft furniture, the absence of the system recommendations to consumers as well many kinds of woodwork and the price of furniture coused consumers had difficulty in determining kinds of wood for furniture, so it is with a lack of knowledge or information to consumers of the type wood so consumers it should prompt about detail kinds of wood for furniture and the price as a result, the process of determining the eat a long time. This Research applies the methods of TOPSIS (Technique for Order Preference by Similarity Ideal Solution), applies the methods of TOPSIS as recommendations and faciliate the consumers in the selection of kinds wood for furniture, and with increase knowledge or information make buyers is more rapidly in determining the wood for furniture. Excess method TOPSIS the concept simple and understandable, computations efficient, and has the ability to measuring performance relative of alternative decision in mathematical from simple (Suhada, 2013). In research applies a methods of TOPSIS can add recommendations consumers in the determination of kinds wood for furniture, facilitate consumers in determining of kinds wood for furniture, and the process of the determination of the type wood for furniture was faster.